Public administration in America - Milakovich , Michael E. (Thomson Wadsworth, 2007)
American public administration is truly exceptional and has limited relevance to the solution of administrative problems in other countries. Nevertheless, it is so widely imitated and viewed as a model that anyone studying Public Administration needs to understand why the American system is exceptional and why its practices are so often irrelevant in other countries. Such an understanding requires a comparative analysis of different regimes based on the same constitutional principles -- i.e. the separation of executive, legislative and judicial powers -- and the identification of the peculiarly American structure of a hybrid bureaucracy